Muslim scholars on dialogue of modern science: issues and responses - Deuraseh, Nurdeng @ Nurdeen; Talib, Ahmad Tarmizi; Muhammad Harun, Husni (AESS Publications, 2011)
As we have known the rhetorical exchanges between Muslim intellectual and their Western counterparts on the relationship between Islam and modern science, has started since more than hundred years old if one takes the debate started by Ernest Renan (d. 1892) in Paris in 1883. The exchanges in the nineteenth-century between Islamic reformer Afghani and the French scholar Ernest Renan, in which they engage in a debate to qualify or disqualify Islam as being capable of producing modern science. This article will examine and highlight Muslim scholars’ view on the modern science and its technology. It is found that the birth of modern science in the West and not elsewhere can be understood if we attributed its birth to the influence of four streams of science- the Arabic, Chinese, Indian, and Egyptian- entering Europe from outside.